2019
DOI: 10.1007/s12672-019-00373-2
|View full text |Cite
|
Sign up to set email alerts
|

The Thyroid Hormone Receptor-RUNX2 Axis: A Novel Tumor Suppressive Pathway in Breast Cancer

Abstract: Metastatic breast cancer is refractory to conventional therapies and is an end-stage disease. RUNX2 is a transcription factor that becomes oncogenic when aberrantly expressed in multiple tumor types, including breast cancer, supporting tumor progression and metastases. Our previous work demonstrated that the thyroid hormone receptor beta (TRβ) inhibits RUNX2 expression and tumorigenic characteristics in thyroid cells. As TRβ is a tumor suppressor, we investigated the compelling question whether TRβ also regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…8,9 Although the mechanisms by which TRβ represses tumorigenesis are not well-defined, TRβ is known to regulate several pathways that are drivers of cancer, including repression of PI3K signaling and repression of RUNX2 expression. 2,3,5,10,11 Our recent transcriptomic analysis in anaplastic thyroid cancer (ATC) cell line revealed TRβ functions to regulate the cancer stem cell population and induction of the JAK1/STAT1 pathway. 12 Prior studies have demonstrated that TRβ exerts a strong antitumor effect in breast cancer cells.…”
mentioning
confidence: 99%
“…8,9 Although the mechanisms by which TRβ represses tumorigenesis are not well-defined, TRβ is known to regulate several pathways that are drivers of cancer, including repression of PI3K signaling and repression of RUNX2 expression. 2,3,5,10,11 Our recent transcriptomic analysis in anaplastic thyroid cancer (ATC) cell line revealed TRβ functions to regulate the cancer stem cell population and induction of the JAK1/STAT1 pathway. 12 Prior studies have demonstrated that TRβ exerts a strong antitumor effect in breast cancer cells.…”
mentioning
confidence: 99%
“…In brief, the work on the HECT E3s expands our understanding of the pathogenesis of hematological diseases, providing novel effectors, whose biological significance and therapeutic interest might be explored in the future, especially considering the development of precision oncology [100][101][102]. This field has opened several novel opportunities, thanks to new algorithms [103][104][105] and artificial intelligence [106], modernizing the field of precision oncology in general [107][108][109] as well as in specific cancers [110][111][112][113]. From this overview, it appears clear that further studies are needed to corroborate the implications of HECT-type E3s in leukemogenesis, to understand the molecular basis of their oncogenic function in hematological disorders, as well as to identify their relevant substrates and regulators.…”
Section: Discussionmentioning
confidence: 99%
“…T3 reduced RUNX2 expression in normal and ATC cells, and TRβ knockdown increased RUNX2, increasing the expression of MMP2, MMP13, cyclin D1, osteopontin (OPN), and cadherin 6. Transfected TRβ also repressed RUNX2 and EMT markers in MDA-MB-231 cells; conversely, TRβ-knockdown in breast epithelial-like MCF10A cells caused an increase in RUNX2 and EMT markers [74]. López-Mateo et al confirmed a decrease in EMT genes such as vimentin and snail family transcriptional repressor 2 (SLUG) in estrogen receptor alpha positive (ER⍺ + ) breast cancer cells [18].…”
Section: Trβ Inhibits Epithelial-mesenchymal Transitionmentioning
confidence: 97%